Initial expierence with Deprescribing in physically active older adults with post-COVID syndrome in Kazakhstan: A Cohort Study Investigating Transition to Simplified Treatment Regimen (Bangladesh Journal of Medical Science, 2025)
Background Arterial hypertension (AH) and post-COVID synrome poses a rising challenge in low and middle-income countries, with uncertain prevalence in Kazakhstan’s older adults population.Objectives This study investigates the effectiveness and safety of transitioning older adults patients (65 and older) from multiple antihypertensive medications to a “single tablet” strategy, aiming to evaluate its effect on patient conidion and identify factors influencing dose adjustments. Design A prospective cohort study with a follow-up of 8 week. Participants There were enrolled 98 patients, categorizing them by age groups 65-74 years and 75 and older. Intervention One-moment isolated deprescribing of hypotensive drugs to “one tablet” therapy. Measurements Endpoints were assessed over three visits in eight weeks, utilizing statistical analysis with significance set at p < 0.05.Results Older patients exhibited a trend of higher education, lower smoking rates, and lower average weight. Transitioning to a single-tablet strategy led to a significant reduction in hypertensive crises and adverse events. While therapy adherence improved initially, it decreased by 10% by the 8th week. Factors influencing therapy changes were identified through subgroup analysis.Conclusion This study provides valuable insights into transitioning older adults patients to a “single tablet” strategy, underscoring the importance of personalized approaches based on identified influencing factors.Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 155-163